Red pigment produced by Zooshikella ganghwensis inhibited the growth of human cancer cell lines and MMP-1 gene expression - Oh, Eun-Ji; Kwon, Jung-Hwa; Kim, Su-Yeon; In, Seo-Ji; Lee, Dong-Geol; Cha, Mi-Yeon; Kang, Hee-Cheol; Hwang-Bo, Jeon; Lee, Youn-Hyung; Chung, In-Sik; Baek, Nam-In (Applied biological chemistry, 2016)
A red pigment produced by Zooshikella ganghwensis , was purified by solvent extraction and fractionation. The pigment was identified to be prodigiosin on the basis of spectroscopic data such as 1 H-NMR, 13 C-NMR, DEPT, 2D-NMR, IR, and FAB-MS. Prodigiosin inhibited matrix metalloproteinase-1 gene expression and the growth of human cancer cell lines, SK-BR-3, HCT-116, SK-OV-3, HeLa, HepG2, and SK-MEL-5.